Tracing the Historical Roots and the Development of Islamic Epistemology from the Early to Modern Periods (A Study of Bayani, Burhani, 'Irfani) - Sifa, Alex Nanang Agus (International Conference of Moslem Society, 2019)
This article is aimed at revealing the emergence and development of islamic epistemology. Epistemology which means the theory of knowledge is not wholly owned by Modern Western scientists with the advance of civilization of them. Before the West advanced, Islam as a religion that upheld science, has its own history of the theory of knowledge or epistemology. In fact, epistemology in Islam recognizes not only tools or sources of knowledge which are in the form of senses or intelligence but also the heart (intuition). These senses, intelligence, and intuition are well known as three epistemological models of Islam (Bayani, Burhani dan ‘Irfani).